Tra historia, ricordi e raccordati medicamenti: la peste di Padova nella cronaca di Alessandro Canobbio - Edoardo Zorzan (Laboratoire Italien)
In the restless context of the second half of the 16th century, in the territories of northern Italy, an inexplicable catastrophe occurred and caused panic among the population. A violent plague epidemic swept through the territories of the states of Milan and Venice, which –trying in every way to counter the emergency– were forced to adopt harsh measures to isolate and control the population. Due to the general discontent and the Counter-Reformation's demands for religious renewal, the plague soon became a terrain for political debate, on which secular power choices clashed with the spiritual interpretations of the renewed Catholic Church. Focusing our interest on the Venetian mainland context, we will here analyse a writing of historical memory born out of the trauma of the epidemic, Alessandro Canobbio's Successo della peste di Padova, an immediate writing in which the Counter-Reformation urgency to recount the truth of the silent disaster clashes with the secular mythology of the Republic of St. Mark. Analysing the structure and narrative strategies of the writing, we will highlight both the peculiar tension that animates Canobbio’s prose and those elements that well inscribe the chronicle of the plague into the historiographical panorama of the second half of the 16th century.